Ethanol Perinatal Exposure Induces Behavioral Alterations and Ethanol Preference in Adolescent Wistar Rats - Aronne, María Paula (2013)
Ethanol-perinatally-exposed (EPE)Wistar rats show central nervous system morphological alterations that persist until adulthood. The aim of this work was to study whether adolescent EPE rats present alterations in behavior and develop ethanol (EtOH) preference. For behavioral analyses, locomotor and exploratory activity, anxiety and long-term memory standardized tests were performed on 40 to 45 dayold male rats. Another group of rats chose to drink between EtOH and water using the model of preference between two bottles, one with EtOH 6% v/v and the other with water. During eight weeks, the volume of EtOH consumed/kg/day was registered and blood EtOH concentration was determined at the end of the experiment. Results in EPE rats show a decrease in aerial exploration and anxiety, while locomotor activity and long-term memory were not affected. Bothmale and female EPE rats preferred EtOH earlier than control rats, showing a highest level of blood EtOH concentration.